AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN ALOKASI DANA DESA (ADD) DI DESA MUARA PANCO TIMUR KECAMATAN RENAH PEMBARAP - Nadia Zein; Addiarrahman; Nurlia Fusfita (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2022)
This study aims to identify and describe the implementation of accountability and transparency in the management of village fund allocations in Muara Panco Timur Village, Renah Pembarap District. The approach method in this research is descriptive qualitative. Sources of data used are primary data obtained by direct interviews and secondary data obtained from related documents. The results of this study indicate that the management of village fund allocations in Muara Panco Timur Overall, starting from accountability and transparency, it is quite good, but still has quite a lot of weaknesses and shortcomings. This is evidenced in the management of village fund allocations, the government has implemented the principle of accountability, namely by involving the community in planning the allocation of village funds (village deliberation), but only until the planning is carried out, the rest is carried out by the village government without involving village officials in managing village funds. then the application of transparency in accordance with the application of the three mechanisms, the application of transparency in the management of village fund allocations in the village of Muara Panco Timur is said to be not good, this is due to the lack of a government that implements the principle of transparency, namely by not fully involving the village community of Muara Panco Timur in managing village funds and lack of transparency in the management of village funds.